Docetaxel followed by abiraterone in metastatic castration-resistant prostate cancer: efficacy and predictive parameters in a large single center cohort - Höfner, Thomas; Vallet, Sonia; Hadaschik, Boris; Pahernik, Sascha; Duensing, Stefan; Hohenfellner, Markus; Jäger, Dirk; Grüllich, Carsten (World journal of urology, 2015)
Purpose To report the outcome and course of disease in patients with metastatic castration-resistant prostate cancer (mCRPC) treated with first-line docetaxel followed by abiraterone acetate in a single center.MethodsIn this retrospective observational study, we reviewed the course of disease of all applicable patients with mCRPC treated with docetaxel followed by abiraterone at our center. We analyzed progression-free survival (PFS) of docetaxel and abiraterone treatments. We further searched for predictive factors for the duration of treatment response.ResultsMedian PFS between initiation of androgen deprivation therapy and the diagnosis of mCRPC was 32 months. Median PFS on docetaxel treatment was 9 months. Median PFS on abiraterone treatment was 11 months. Patients with higher Gleason scores (GS) (8-10) at initial diagnosis had a significantly longer median PFS on docetaxel as compared to patients with GS 6-7, p = 0.01. We demonstrate a significant correlation between the PFS on docetaxel and PFS on abiraterone in the post-docetaxel setting (Kendall tau r = 0.32, p = 0.019) as well as a significant negative correlation between the PSA nadir under abiraterone treatment and the time to progression under abiraterone (Kendall tau r = −0.43, p = 0.007).ConclusionsHigh Gleason score appears to be predictive of duration of response to docetaxel. Interestingly, progression-free survival with abiraterone appears to be correlated with the duration of response with docetaxel, whereas PSA decline and low nadir appear to be predictive of response to abiraterone.